Integrated superconducting coil into PV generator for power smoothing and voltage regulation - Kreeumporn, Worapong; Ngamroo, Issarachai (My University, 2016)
At present, the installation of PV and plug-in hybrid electric vehicles (PHEVs) tends to increase significantly in the power distribution system. The PV power output varies due to the weather condition while the battery charging in PHEVs causes the voltage fluctuation. To smooth the PV power and regulate the voltage, this paper focuses on the new application of superconducting coil (SC) which is integrated into the photovoltaic (PV) generator. The SC is connected to the DC side of the PV generator via a DC-to-DC converter. With the proportional integral (PI) controls for the DC-to-DC converter of the SC and the inverter of the PV, the stored energy in the SC can be controlled to smooth the PV power and suppress the voltage fluctuation. Simulation results show the effectiveness of the PV with SC in comparison with the PV without SC.
Keywords: photovoltaic generator; plug-in hybrid electric vehicle; power smoothing; superconducting coil; voltage regulation